Quantitative evaluation of the Gingival Zenith position and Papilla proportions in the maxillary anterior dentition - DR. BHARATHI.S.R,; DR .PRIYANKA K CHOLAN,; DR. PSG PRAKASH,; DR.DEVAPRIYA APPUKUTTAN,; DR. DHAYANAND JOHN VICTOR,; DR. SUMI PRIYADHARSHINI.S, (International Journal of Pharma and Bio Sciences, 2017)
Gingival morphology, contour and visibility play an essential role in creating a beautiful smile and these significant soft tissue considerations need to be established during the treatment planning requiring reconstructionor rehabilitation in the anterior esthetic zone. These anatomical landmarks show variations based on the race and ethnicity of the study population therefore, understanding and establishing the variations is a prerequisite to create a predictable esthetic smile during anterior oral rehabilitation. Keeping this objective in mind, the present study was undertaken to establish the position and to quantify the distance of gingival zenith (GZ) from the vertical bisecting midline (VBM) in the maxillary anterior tooth region. Additionally, we also aimed to quantify mesial and distal papillary proportions in relation to clinical crown length. A total of 55 subjects were recruited based on inclusion and exclusion criteria. Following which maxillary alginate impressions were made and poured with dental stone. The GZ position and the distance of GZP from VBM were measured using a digital vernier caliper under 2.5x optical magnification loupes. The mesial and distal interdental papillary heights were marked on the casts and divided by the clinical crown length to establish mesial and distal papilla proportion for each maxillary anterior tooth. On analysis it was seen that the central incisors, lateral incisors and canines showed distal displacement of 0.8mm, 0.6 mm and 0.5 mm respectively. Mean MPP and DPP for maxillary anterior dentition were 45.2% and 44.8 % respectively. The central incisors showed statistically significant difference between MPP and DPP (p value 0.026). The GZP was predominantly distally placed in relation to VBM in all the maxillary anterior teeth. The central incisors showed significant difference in mesial and distal papilla proportion, whereas canines showed a trend towards increased distal papillary height.